PENGARUH PROGRAM LITERASI SEKOLAH TERHADAP MINAT BACA SISWA - Ahmad, Amelia; Panigoro, Meyko; Maruwae, Abdulrahim; Hasiru, Roy; Bahsoan, Agil (Damhil Education Journal, 2024)
School literacy programs are a very important effort in increasing students' interest in reading. Through this program, students are introduced to various types of reading material that are interesting and relevant to their lives. The existence of a school literacy program is the main key in presenting a variety of quality reading materials in the school library. With easier access to quality books, it is hoped that students will become more interested in reading and develop their interest in reading. The objective of this study was to determine to what extent the influence of the school literacy program on the reading interest of class VIII students at SMP Negeri 3 Kota Gorontalo. This study used a quantitative collaborative approach with a sample size of 56 students. Data collection techniques used were observation, questionnaires, and documentation, while data analysis techniques in this study used simple regression. The research findings revealed that there was a positive and significant influence between the school literacy program on the reading interest of Class VIII students at SMP Negeri 3 Kota Gorontalo. The coefficient of determination from the regression model previously obtained was 0.331, indicating that 33.1% of the variation in school literacy program could be explained by students' reading interests. In other words, the better the school literacy program is implemented, the more students will be interested in reading. Meanwhile, the remaining value resulting or influenced by other variables not examined in this study was 66.9%.